(untitled) - Weller, Joel Ira (Wallingford, UK, 2009)
Quantitative Trait Loci (QTL) is a topic of major agricultural significance for efficient livestock production. This advanced-level textbook covers all the statistical methods that have been used or proposed for detection and analysis of QTL and marker- and gene- assisted selection in animal genetics and breeding, as well as new advances that have revolutionized the field since the first edition.
Keywords: Livestock,Livestock,Quantitative genetics,Vật nuôi,Vật nuôi,Biến đổi di truyền; Breeding,Genetics,Sự nhân giống,Di truyền